Clinicopathologic Significance of SATB1 and DJ-1 Proteins Expression in Cervical Carcinoma - Tawadros, Ashraf Ishak Fawzy; Khalafalla, Mohamed Mohamed Mohamed (Annals of Pathology and Laboratory Medicine, 2018)
Background: Special AT-rich sequence binding protein 1 (SATB1) and DJ-1 proteins play a crucial role in tumorigenesis and tumor progression in many human malignancies. Limited data is available in literature about their role in cervical carcinomas. Aims: The present study was designed to investigate the immunohistochemical expression of SATB1 and DJ-1 proteins in cervical carciÂnoma and their relationships to clinicopathologic variables. Material and Methods: Tissue sections from 100 cervical lesions distributed as 60 cases of cervical carcinoma, 30 cases of squamous intraepithelial lesion (SIL) and 10 cases with normal cervical tissue were evaluated for SATB1 and DJ-1 proteins expression by immunohistochemistry. Results: SATB1 expression was detected in 41.7% of cervical carcinomas versus 20% and 6.7% of HSIL and LSIL, respectively (p = 0.019). A significant positive correlation between SATB1 expression to lymph node metastasis (p = 0.004) and pTNM (p = 0.028) was noted. DJ-1 expression was detected in 68.3% versus 33.3% and 13.3% of HSIL and LSIL, respectively (p = 0.001). A significant positive association between DJ-1 expression and lymph node metastasis (p = 0.037) was noted. Normal cervical tissue was negative for SATB1 and DJ-1 expression. A significant positive association between SATB1 and DJ-1 immunoreactivity was detected in investigated cervical carcinomas (p = 0.027). Conclusions: SATB1 and DJ-1 are shown to be promising potential prognostic biomarkers in cervical carcinoma since their overexpression is correlated with advanced clinicopathologic variables including lymph node metastasis. SATB1 and DJ-1 can be promising therapeutic targets for cervical cancer.